JOB SATISFACTION SCALE FOR TECH WORKERS: IMPLEMENTATION COMPASS - Ehigbochie, Amenawon Imuwahen; Ekuobase, Godspower Osaretin (FUDMA Journal of Sciences, 2024)
Tech workers are not just employees but ubiquitous architects and drivers of the imminent digitalized future. Tech worker’s wellbeing is, therefore, crucial for global prosperity – necessitating their continuous monitoring and management in the workplace. Although a cross-cultural job satisfaction scale has been specifically developed and validated to help gauge the wellbeing of tech workers, christened JSST, it lacked an implementation guideline. This lack of implementation guidelines for the JSST questionnaire can stifle its practicality and, by extension, the wellbeing of Tech workers. The aim of this study, therefore, is to design an implementation guideline for JSST. The implementation guideline was designed using descriptive statistics and algorithmic specification. Adopting a self-assessment online survey on the original Five-point Likert JSST Questionnaire, this study also demonstrated the implementation of the guideline. 276 valid Tech workers’ job satisfaction self-assessment data solicited globally using the JSST questionnaire was employed to demonstrate the guideline’s feasibility. Overall, the job satisfaction index of the global tech workers has been estimated to fall into the third quartile of satisfaction, Q3, which is low. This low satisfaction index may account for the high turnover and turn-away in the global Tech industry. A notable outcome of this study is the seamless JSST implementation scheme, which is not only effective but also highly adaptable. This scheme can be tailored for the implementation of any multi-faceted psychometric scale, making it a versatile tool for assessing employee wellbeing. The automation for web accessibility of the JSST implementation scheme is encouraged.